Plight of Widows in Hindu Religion (A Feminist Critique of Deepa Mehata’s Film Water) - Ramesh Prasad Adhikary (Research Synergy Foundation, 2020)
This research paper is focused in Deepa Mehta's Film Water to study the plight of Hindu widows. As the tradition of Hindu society, widows are compelled to adopt the widow system. Chuyia, the eight year old protagonist is sent to a Bidhuwa Ashram in Benaras because of her widowhood. The exploitation of child-marriage in the grip of patriarchal culture of widowhood, and the rejection of Chuyia to accept her widowhood is presented in the film. Kalyani, the second young widow in the ashram, revolts against such inhuman culture and decides to get married. She is forced to act as a 'prostitute' in the house of bourgeois. Chuyia is also sexually exploited by bourgeois. As a qualitative research, the researcher analyzed the film from the perspective of Hindu evil traditions. Patriarchies, widow tradition, social stereotypes of Hindu traditions are observed in this paper to analyze the film.